2015
DOI: 10.3844/ajeassp.2015.717.729
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Anchoring in Foundations of Wind Turbine Towers

Abstract: Tubular steel towers are the most common supporting structure of wind converters. The towers' foundation covers an important part of the initial cost and its configuration depends heavily on the type of subsoil. Onshore structures are founded on spread footing foundations or pile foundations with the first being the commonest. In these spread footing foundations, the tower is either embedded in the concrete foundation slab or the tower bottom flange is anchored to the concrete by means of pretensioned bolts. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…McAlorum et al [2] monitored cracks on the surface of the WT foundation with FBG-based long-gauge strain sensors, and in this paper, the cracks on the surface of the WT's foundation are divided into three types: reactive, permanent, and behavioral, and are described in detail. At the same time, large tensile and compressive forces are transferred to the foundation by the ESR, and the concrete in the anchorage zone of the ESR is subjected to high-cycle fatigue loading, causing concrete in foundations to operate at higher stress [3][4][5][6]. If things continue this way, the concrete in the compressive zone of the WT foundation may experience high cycling, resulting in fatigue accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…McAlorum et al [2] monitored cracks on the surface of the WT foundation with FBG-based long-gauge strain sensors, and in this paper, the cracks on the surface of the WT's foundation are divided into three types: reactive, permanent, and behavioral, and are described in detail. At the same time, large tensile and compressive forces are transferred to the foundation by the ESR, and the concrete in the anchorage zone of the ESR is subjected to high-cycle fatigue loading, causing concrete in foundations to operate at higher stress [3][4][5][6]. If things continue this way, the concrete in the compressive zone of the WT foundation may experience high cycling, resulting in fatigue accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Fujiyama [10] analyzed the stability of wind turbine support structures by defining their vibration characteristics using field-monitoring data. Examining the fatigue characteristics of wind turbine foundations, Stavridou [11] found that the diameter of the tower bottom significantly affected fatigue life. He [6] observed the internal stresses in a wind turbine foundation and found that the primary external load was borne by the base flange of the foundation ring.…”
Section: Introductionmentioning
confidence: 99%
“…Most onshore wind turbines are built on extended foundations, which are divided into gravity foundations and anchor pile foundations. As shown in Figure 3, there are two ways to connect the tower and the foundation in the extended foundation: one is to embed the tower directly into the concrete foundation slab ('foundation ring'); the other is to fix the bottom flange of the tower on the concrete by using prestressed bolts ('anchor cage ring') [26]. The foundation ring is widely used because of its simple structure, large production, convenient quality control, and convenient installation [28,29].…”
Section: Introductionmentioning
confidence: 99%